2016
DOI: 10.1002/dc.23426
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the adequacy of Hologic® Cervista® HPV HR results on ThinPrep® Pap samples treated with glacial acetic acid

Abstract: The levels of genomic DNA were significantly decreased in GAA treated vs non-treated TP samples. Aliquoting from the TP sample prior to treatment with GAA enables accurate measurement of DNA without affecting the adequacy of the TP cytology slide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…To our knowledge, all related studies of GAA have been reported only in pathology journals. [1][2][3][4][5][6][7][8][9][10][11][12] Because not all laboratories offer this method, clinicians should inquire about the use of GAA in the laboratory responsible for interpreting their patients' specimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, all related studies of GAA have been reported only in pathology journals. [1][2][3][4][5][6][7][8][9][10][11][12] Because not all laboratories offer this method, clinicians should inquire about the use of GAA in the laboratory responsible for interpreting their patients' specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the number of uninterpretable cervical smear tests that are unsatisfactory for evaluation would aid efforts to prevent cancer through earlier detection and would avoid costly repeat testing. Cost‐effective laboratory methods, such as adding glacial acetic acid (GAA) during slide processing of ThinPrep (TP) (Hologic, Marlborough, MA, USA) cervical smear test specimens, can improve the detection of early disease in bloody samples . GAA improves the visibility and cellularity of epithelial cells by lysing the erythrocytes in the blood that clings to the filter during slide processing .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation